Push Notification Using the Websocket in the Application of Sistem Informasi Uji Kompetensi Online (Situk) Version 2 (Future Science, 2021)
SITUK-V2 is an application of the second version of the online competency test integrated system, which is used in the competency test at the LSP (Lembaga Sertifikasi Profesi) UPN